Tuning organic magnetoresistance in polymer-fullerene blends by controlling spin reaction pathways - Janssen, Paul; Cox, Mark G. D. M.; Wouters, S. H. W.; Kemerink, Martijn; Wienk, Martinus Maria; Koopmans, Bert (Nature Communications, 2013)
Organic semiconductors could be useful in spintronic devices if their reactions to magnetic fields can be controlled appropriately. Here, the authors show that the exact choice of materials alters the dominant mechanism of the spin interactions, thus tuning the organic magnetoresistance.